Organic versus conventional: A comparative study on the shelf life of passion fruit (Passiflora edulis Sims) crops (2019)
Yellow passion fruit (Passiflora edulis Sims) is one of the most appetising fruits worldwide due to its intense flavour. There have been few published studies comparing the evolution of storage quality parameters and shelf life of organic and conventional tropical fruit crops. The aim of the present work was therefore to compare the temporal changes in various physicochemical parameters and commercial shelf life of fresh organic passion fruit (OPF) and conventional passion fruit (CPF), under the same storage (20.0 ± 1.0°C, 85.0 ± 2.0% relative humidity) and initial maturity conditions. Colour measurements and total soluble solid contents showed significant differences between OPF and CPF. Increasing colour difference (ΔE) and decreasing hue angle values were observed during the storage in both crops. Nonetheless, the rate of growth of ΔE in CPF was higher than that in OPF. In contrast, the initial temporal rate of reduction in the hue angle was more rapid in CPF. Total solid soluble content remained almost unaltered during the observation period, and there were insignificant differences in the measured values between OPF and CPF. Firmness and active acidity did not manifest significant differences between the crops. The same loss of weight (30.0% ± 1.0%) was observed in both crops at the end of the storage period. © 2008 IFRJ, Faculty of Food Science & Technology, UPM.